2017
DOI: 10.3390/nu9070750
|View full text |Cite
|
Sign up to set email alerts
|

Is Sweet Taste Perception Associated with Sweet Food Liking and Intake?

Abstract: A range of psychophysical taste measurements are used to characterize an individual’s sweet taste perception and to assess links between taste perception and dietary intake. The aims of this study were to investigate the relationship between four different psychophysical measurements of sweet taste perception, and to explore which measures of sweet taste perception relate to sweet food intake. Forty-four women aged 20–40 years were recruited for the study. Four measures of sweet taste perception (detection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 61 publications
(100 reference statements)
9
106
4
1
Order By: Relevance
“…Previous data investigating the link between sweetness liking, BMI, and intake of sweet foods is conflicting, with most data failing to find any significant associations (Drewnowski, Kurth, & Rahaim, ; Malcolm et al., ; Rodin, ; Simone & Pangborn, ; Thompson, Moskowitz, & Campbell, ; Thompson et al., ; Witherly, Pangborn, & Stern, ; Wooley et al., ). However, in a more controlled experiment, one recent study using 44 female participants did showed a positive relationship between liking of fruit drink and hedonic liking ratings of sweet glucose solutions (Jayasinghe et al., ). Similarly, at present, we also found no significant differences in terms of complex carbohydrate liking (solutions and prototypical foods), BMI, and frequency of consumption of complex carbohydrate based foods.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data investigating the link between sweetness liking, BMI, and intake of sweet foods is conflicting, with most data failing to find any significant associations (Drewnowski, Kurth, & Rahaim, ; Malcolm et al., ; Rodin, ; Simone & Pangborn, ; Thompson, Moskowitz, & Campbell, ; Thompson et al., ; Witherly, Pangborn, & Stern, ; Wooley et al., ). However, in a more controlled experiment, one recent study using 44 female participants did showed a positive relationship between liking of fruit drink and hedonic liking ratings of sweet glucose solutions (Jayasinghe et al., ). Similarly, at present, we also found no significant differences in terms of complex carbohydrate liking (solutions and prototypical foods), BMI, and frequency of consumption of complex carbohydrate based foods.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of prospective nutrition teachers, no significant associations were observed between sweetness preference and several variables, including physical activity level, stress level, sleep, weight gain, or constipation [122]. In four cross-sectional studies, significant positive correlations were identified between sweetness preference and several different variables, including sweet taste sensitivity, fasting blood glucose level, basal metabolic rate, body weight index [123]; total energy and carbohydrate (total sugar, fructose, glucose) intakes [124]; country of residence, age, and BMI [125]; and age, current smoking status, stronger cognitive restraint, and former dieting ( [30]; refer to Table S3-12 of Supplementary File S3 for gender-specific results). Lampuré et al [30] found significant negative correlations between sweetness preference and uncontrolled eating habits and emotional eating habits (see Table S3-12 of Supplementary File S3 for gender-specific results).…”
Section: Other Factors and Sweetness Preferencementioning
confidence: 99%
“…According to Wilk test, the distributions were always normal. Children were divided into 3 groups according to the 25 th 179 and 75 th percentiles calculated across total sample: ''low food neophobia'' (children in the lowest quartile, 180 scores ≤ 17), ''high food neophobia'' (children in the highest quartile, scores ≥ 24) and ''medium food 181 neophobia'' (children in the mid 50%, scores [18][19][20][21][22][23]. Reliability of the tool in different EU countries 207…”
Section: Data Analysis 175mentioning
confidence: 99%